PERIODE KRITIS KEKERINGAN PADA PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L.) - Ahmad Arsyadmunir, (Agrovigor, 2016)
Mungbean (Vigna radiata L.) is one of the food commodities that consumed by general society be side of rice. One of effect that are not optimal production is drought stress. This research aims to study the critical period due to drought  stress  of mungbean  crop and  its  impact  on  growth  and  the  yield  of production.  This  study  uses  a  Completely  Randomized  Design  (CRD)  non factorial with 4 treatments, A0 (watering until harvest), A1 (without watering at the age of 15 - 28 days), A2 (without watering at the age of 29 - 42 days) and A3 ( without watering at the age of 43 - 56 days). Lowest average value of plant height and number of leaves derived from the treatment A1 with stress time at the age of 15 - 28 days after planting or when the end of the vegetative phase. While the lowest average value of seeds weight per crop and total number of pods derived from treatment A2 with stress time at the age of 29 - 42 days after planting or during pod formation phase.Key words: mungbean, growth, production, drought stress